The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1021/jp068880c
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous versus Heterogeneous Catalysis at Electrodes Modified with a Thin Organic Layer:  Theoretical and Experimental Study under Conditions of Square-Wave Voltammetry

Abstract: A catalytic mechanism at thin film-modified electrodes is studied both theoretically and experimentally under conditions of square-wave voltammetry (SWV). The electrode system considered consists of a solid electrode covered with an electrochemically inactive thin film (e.g., a layer of a water-immiscible organic solvent) containing a neutral redox probe (R 1 ). The modified electrode is immersed in an electrolyte solution (typically an aqueous electrolyte solution) that contains a second redox probe (R 2 ) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…The more general case, including a quasireversible electrode reaction, was briefly addressed in a recently published monograph [18]. Later on, the theory was extended to encompass surface electrode processes, where both components of the redox couple are firmly immobilized on the electrode surface [21], as well as complex electrocatalytic mechanisms encountered with thin electroactive films [22].…”
Section: Introductionmentioning
confidence: 99%
“…The more general case, including a quasireversible electrode reaction, was briefly addressed in a recently published monograph [18]. Later on, the theory was extended to encompass surface electrode processes, where both components of the redox couple are firmly immobilized on the electrode surface [21], as well as complex electrocatalytic mechanisms encountered with thin electroactive films [22].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the voltammetric response of TFE is particularly sensitive to all phenomena affecting the properties of the L/L interface. In the presence of another redox species in the aqueous phase, the overall electrochemical reaction could additionally involve a heterogeneous electron-exchange reaction across the L/L interface [1,6]. In the course of the repetitive potential cycling the metal deposition is manifested as a decreasing of the voltammetric response (inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…the three-phase electrodes) [2], are a useful tool for studying complex electrochemical processes where the electrode reaction is coupled with an ion-transfer across a L/L interface. Their application ranges from determination of thermodynamic [2,3] and kinetic parameters of ion [4,5] and/or electron transfers [1,6], mechanistic [7] and biomimetic studies of membrane processes [8], to bioelectroanalysis [9,10]. Besides, it has been demonstrated that TFE are an excellent scaffold for studying metal nanoparticle deposition at the L/L interfaces [11], which is a unique environment due to its molecular smoothness [12].…”
Section: Introductionmentioning
confidence: 99%
“…Their application spans over analysis of ion [11][12][13][14] or electron-transfer [15,16] reactions across liquid|liquid (L|L) interface, study of the mechanism of redox transformation in the organic film [17][18][19], nanoparticle preparation [20], electrocatalysis [21], and bioelectrochemical studies of redox-inactive proteins [22,23]. The thin-film electrode is a rather simple system that consists of graphite electrode (GE) covered with a thin, micrometer-dimension film, of a water immiscible organic solvent (O).…”
Section: Introductionmentioning
confidence: 99%